(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In traditional pragma linguistics, the main focus is on the speaker’s communicative goal, and the listener’s participation in meaning-content formation is not given much importance. Speech creativity and context are interrelated phenomena. It also mentions the need for context elements to be mutually adapted in the process of communication.